Strategies For The Use of Social Media In Promotions On Poyalisa Island, Central Sulawesi - Said, Farid; Amirullah, Amirullah; Raihansyah, Moh.; Kurniawan, Kurniawan (Asian Journal of Social and Humanities, 2024)
Advances in information and communication technology through Social Media which have been used by Poyalisa Island because with social media of course the potential for increasing tourist visits will increase in number, apart from that social media is a tool where young people who are often called millennials make it a platform that is very used in carry out promotions. The behavior and interests of tourists who visit a destination as a result of promotion via social media can be known through studies based on the Technology Acceptance Model (TAM) approach and engagement rate. These two approaches are widely used by companies or destination managers to understand tourist behavior and interests with the aim of increasing tourist visits. In this research, the researcher used a descriptive qualitative approach, namely by providing an explanation or description of the problems faced and supported by primary and secondary data. Meanwhile, the data collection used by researchers is observation, interviews, documentation. Where in the research there are three problem formulations, namely Social Media Platform Form, External Factors, and Internal Factors, Social Media Promotion, and Promotion Strategy. Poyalisa Island has its own charm in the Togean Islands, apart from that, its underwater charm and landscape are very pleasing to the eye. The use of social media will indeed have a good impact on increasing tourist visits. Efforts to plan interesting content are certainly one aspect that is very helpful in promotion and content creation efforts. The social media platforms that are influential on Poyalisa Island are Instagram and websites.